(untitled) (Studia Prawnicze / The Legal Studies, 2020)
W artykule przedstawiono kwestię możliwości potwierdzenia przez stronę czynności dokonanych przez osobę działającą jako pełnomocnik strony, która jednak nie może być pełnomocnikiem w postępowaniu cywilnym. Zgodnie z Kodeksem postępowania cywilnego strony i ich organy lub przedstawiciele ustawowi mogą działać przed sądem osobiście lub przez pełnomocników. Katalog osób mogących być pełnomocnikami został ściśle określony w ustawie procesowej i ma charakter zamknięty. Na tle tej regulacji w orzecznictwie sądów dostrzegana jest rozbieżność poglądów w odniesieniu do skutków występowania w charakterze pełnomocnika procesowego osoby nieuprawnionej oraz możliwości ewentualnego zatwierdzenia czynności dokonanych przez taką osobę. Z jednej strony wskazuje się, że w razie potwierdzenia czynności wyłączona jest możliwość uznania postępowania za nieważne na podstawie art. 379 pkt 2 k.p.c. Z drugiej strony podkreśla się, iż sytuacja taka zawsze prowadzi do nieważności postępowania wobec braku należytego umocowania pełnomocnika. Artykuł przedstawia poglądy prezentowane w doktrynie i judykaturze. Autor przeprowadził analizę interpretacyjną przepisów umożliwiających zastępowanie stron postępowania przez pełnomocników, opisując rozbieżne poglądy, prowadząc do końcowych konkluzji, wskazujących na bezwzględną nieważność czynności dokonanych przez osoby, które w ogóle pełnomocnikiem być nie mogły. The text presents the issue of the possibility of a party confirming actions in proceedings carried out by a person acting as a party’s representative, who, however, is not eligible to be a representative. According to the Code of Civil Procedure, parties and their organs or statutory representatives may personally act before a court, or through proxies. The catalog of those who may be proxies has been strictly defined in the procedural act and is exhaustive. In the context of this regulation, the judicature presents different views on what are the results of actions undertaken by a person from outside of this catalogue, who is yet acting as a proxy and the possibilities of validating the action undertaken by such a person. According to one view, in case of validation of the actions undertaken by such person, it is impossible to consider the entire proceeding as invalid according to article 379 point 2 of the Code of Civil Procedure. According to a different approach, such a situation always leads to invalidation of the proceeding due to the proxy’s lack of empowerment. The article presents a broad perspective of the views expressed in the literature, especially prominent specialists dealing with the issues of civil proceedings, as well as a wide range of resolutions and rulings of the Supreme Court. The author conducts an in-depth interpretative analysis of the provisions enabling parties to be replaced by proxies, describing completely divergent views leading to the final conclusions closest to the author. The study presents a prevailing line in doctrine and case law, also supported by the author of the study, indicating the stabilization of legal thought in relation to the mandatory rules of Polish civil procedure. It a significant point that actions are recognized as unconditionally invalid when carried out by persons who are not eligible to be a representative at all.